Increased sea ice melt as a driver of enhanced Arctic phytoplankton blooming - Andrew P. Castagno; Till J. W. Wagner; Mattias R. Cape; Conner W. Lester; Elizabeth Bailey; Catharina Alves‐de‐Souza; Robert A. York; Alyson H. Fleming (Global Change Biology, 2023)
Phytoplankton primary production in the Arctic Ocean has been increasing over the last two decades. In 2019, a record spring bloom occurred in Fram Strait, characterized by a peak in chlorophyll that was reached weeks earlier than in other years and was larger than any previously recorded May bloom. Here, we consider the conditions that led to this event and examine drivers of spring phytoplankton blooms in Fram Strait using in situ, remote sensing, and data assimilation methods. From samples collected during the May 2019 bloom, we observe a direct relationship between sea ice meltwater in the upper water column and chlorophyll a pigment concentrations. We place the 2019 spring dynamics in context of the past 20 years, a period marked by rapid change in climatic conditions. Our findings suggest that increased advection of sea ice into the region and warmer surface temperatures led to a rise in meltwater input and stronger near‐surface stratification. Over this time period, we identify large‐scale spatial correlations in Fram Strait between increased chlorophyll a concentrations and increased freshwater flux from sea ice melt.